2019
DOI: 10.1002/mc.23089
|View full text |Cite
|
Sign up to set email alerts
|

Role of miR‐214 in regulation of β‐catenin and the malignant phenotype of melanoma

Abstract: Wnt/β‐catenin signaling plays an important role in melanocyte biology, especially in the early stages of melanocyte transformation and melanomagenesis. β‐catenin, encoded by the gene CTNNB1, is an intracellular signal transducer of Wnt signaling and activates transcription of genes important for cell proliferation and survival. Wnt/β‐catenin signaling is frequently activated in melanoma through oncogenic mutations of β‐catenin and elevated β‐catenin levels are positively correlated with melanoma aggressivenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Overexpression of miR-1275 promoted cancer cell migration, invasion, and proliferation ( 18 ), which may be related to its negative regulation on the downstream target genes (such as leucine zipper putative tumor suppressor 3) and then to enhance the stemness of cancer cells ( 17 ). Knockdown of ANKRD6 was revealed to increase melanoma cell proliferation and migration ( 19 ). Consistent with these studies, we also identified CD27-AS1 and ANKRD6 were downregulated, while miR-1275 was upregulated in recurrent CC tissues compared with non-recurrent controls.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of miR-1275 promoted cancer cell migration, invasion, and proliferation ( 18 ), which may be related to its negative regulation on the downstream target genes (such as leucine zipper putative tumor suppressor 3) and then to enhance the stemness of cancer cells ( 17 ). Knockdown of ANKRD6 was revealed to increase melanoma cell proliferation and migration ( 19 ). Consistent with these studies, we also identified CD27-AS1 and ANKRD6 were downregulated, while miR-1275 was upregulated in recurrent CC tissues compared with non-recurrent controls.…”
Section: Discussionmentioning
confidence: 99%
“…And these circRNA-miRNA-mRNA regulatory networks may play an important role in the pathological mechanism of vitiligo. For instance, hsa-miR-149-5p targets genes SEMA4D (ENSG00000187764) and ANKRD6 (ENSG00000135299) are involved in regulating melanocyte survival and growth ( Soong et al, 2012 ; Prabhakar et al, 2019 ). Sema4D is a paracrine factor that protects normal human melanocytes to survive under ultraviolet (UV) radiation.…”
Section: Discussionmentioning
confidence: 99%
“…In patients who undergo targeted therapy with BRAF (v-raf murine sarcoma viral oncogene homolog B1) and MEK (mitogen-activated protein kinase) inhibitors the expression of downregulated miRNA-579-3p is associated with treatment resistance, but miRNA-126-3p is responsible for increasing the sensitivity in dabrafenib-resistant patients [ 96 , 97 ]. Chemosensitivity of the malignant cells was correlated with the expression of miRNA-211 but the sensitivity to MAPK inhibitors is decreased when miRNA-214 is overexpressed [ 98 , 99 ]. Referring to immunotherapy in melanoma, the most innovative treatment option implemented so far, miRNAs can be further used as blood markers for efficacy by measuring their plasmatic levels before starting the treatment [ 100 ].…”
Section: Discussionmentioning
confidence: 99%